T CELL EPITOPES OF THE ESXA FULL GENE OF MYCOBACTERIUM TUBERCULOSIS FROM SPUTUM OF MDR-TB PATIENTS - Dewi, Desak Nyoman Surya Suameitria; Soedarsono, Soedarsono; Mertaniasih, Ni Made (African Journal of Infectious Diseases (AJID), 2018)
Background: In 2015, World Health Organization (WHO) discovered 10.4 million tuberculosis (TB) cases around theworld. Multidrug-resistant tuberculosis (MDR-TB) became a threat because it has high mortality number. There were480,000 new MDR-TB cases in 2015. Based on those problems, diagnostic development to detect M. tuberculosisrapidly and accurately is needed. The importance of detecting epitope expression of esxA full gene because there was apotential of complexity over the protein structure and might affect the protein concentration. By knowing epitopeprediction, there’s an expectation that it can help the development of TB diagnostic. This research was aimed todetermine the T cell epitope prediction of esxA full gene from MDR-TB patientsMaterial and Methods: Total of 24 MDR-TB sputum isolate from TB patients at Dr. Soetomo Hospital were collectedfrom September to December 2016. Samples were confirmed as MDR-TB using GeneXpert and Bactec MGIT 960.Those samples tested using PCR targeted 580 bp of esxA gene and sequencing. Gene sequence was aligned against wildtype using Bioedit program version 7.2.5 and NCBI BLAST. T cell epitope prediction was analyzed by GENETYXversion 10.Results: Epitope predictions that could be obtained were IEAAAS, ASAIQG, VTSIHS, TKLAAA, VTGMFA basedIAd Pattern Position and EAAAS based Rothbard/Taylor Pattern Position. Those prediction epitopes can determine theseverity of disease, therefore full gene of esxA could be used as diagnostic target.Conclusion: This research discovered five specific T cell epitope prediction based on IAd Pattern Position and oneepitope prediction according to Rothbard/Taylor Pattern Position.